Occurrence of extended-spectrum beta-lactamases in Enterobacteriaceae isolated from hospitalized patients in Curitiba, southern Brazil - Nogueira,Keite da Silva (2006)
Production of extended-spectrum beta-lactamases (ESBL) by enterobacteria is an important resistance mechanism against antimicrobial beta-lactamics. We tested 498 bacterial strains isolated from two tertiary-care teaching hospitals for ESBL production, using screening breakpoints for aztreonam and third generation cephalosporins, according to CLSI recommendations. Among these isolates, 155 were positive for the ESBL screening test, and 121 (78%) were confirmed by the clavulanic acid combination disk method. We found a high frequency of ESBL (24%) among Enterobacteriaceae, with a frequency of 57.4% for Klebsiella pneumoniae, 21.4% for Klebsiella oxytoca, and 7.2% for E. coli. In other members of Enterobacteriaceae, non-Klebsiella and non-E. coli, the prevalence was 21.6%. Ceftriaxone and cefotaxime showed a higher sensitivity in the screening test (99.2%) when compared to ceftazidime, aztreonam and cefpodoxime. However, cefotaxime/cefotaxime plus clavulanic acid showed a higher sensitivity in the confirmatory test (96.7%).